KINERJA E-COMMERCE SEBAGAI SALAH SATU PENUNJANG REVENUE DI CAVINTON HOTEL YOGYAKARTA - Prasetyo, Sigit; Hery Krestanto; Fajar Amanda Putra (Bajang Institute, 2025)
This research explores the role of e-commerce as a revenue enhancer at Cavinton Hotel Yogyakarta amidst the growing digitalization of the tourism and hospitality industries. With Yogyakarta’s position as a leading tourist destination in Indonesia and the increasing number of domestic and international visitors, hotels are required to adapt by integrating digital technologies into their marketing and reservation systems. Cavinton Hotel Yogyakarta has embraced this transformation by implementing comprehensive e-commerce strategies through Online Travel Agents (OTAs), digital promotion, and reservation platforms. The research identifies the Standard Operating Procedures (SOPs) used in managing e-commerce functions such as rate setup, booking coordination, competitor analysis, and revenue monitoring, all of which contribute to business performance and operational efficiency. The findings show that the hotel’s e-commerce performance—particularly in the Front office department—has significantly improved revenue outcomes over the six-month evaluation period. The study supports existing literature which emphasizes the importance of digital transformation in achieving business agility and customer satisfaction in the hospitality sector. Cavinton Hotel Yogyakarta serves as a model of how strategic digital adaptation, when supported by skilled human resources and consistent service standards, can offer a competitive advantage in an increasingly digital tourism market. The insights from this research are expected to be useful for other hotels seeking to optimize their digital revenue strategies in the post-pandemic era.